Interaction between estuarine microphytobenthos and physical forcings: the role of atmospheric and sedimentary factors - Pan, Jerónimo (2013)
The goal of this study was to analyze microbial mats and biofilms from the lower supratidal area of the Bahía Blanca estuary (Argentina), and explore their relationship with sediments and other physical forcings. Thirteen monthly sediment samples (uppermost 10 mm) were taken and their composition and abundance in microorganisms was determined by microscopy. Physical parameters (solar radiation and sediment temperature at −5 cm) were recorded with a frequency of 5 minutes by a coastal environmental monitoring station. Additionally, sediment grain size and moisture content were determined for distinct layers in the uppermost 20 mm, and the rate of inundation of the supratidal area was estimated from tidal gauge measurements. There were significant seasonal differences in the biomass of the microphytobenthic groups considered (filamentous cyanobacteria and epipelic diatoms), with the former consistently making up >70% of the total biomass. The relationships between microphytobenthos and sediment temperature and solar radiation fitted to linear regressions, and consistently showed an inverse relationship between microphytobenthic abundance and either one of the physical parameters. The granulometric analysis revealed a unimodal composition of muddy sediments, which were vertically and spatially homogeneous; additionally, there were significant seasonal differences in water content loss with drying conditions prevailing in the summer. Several Microbially-Induced Sedimentary Structures (MISS) were identified in the supratidal zone such as shrinkage cracks, erosional pockets, gas domes, photosynthetic domes, mat chips and sieve-like surfaces. In contrast to studies from analogous environments in the Northern Hemisphere, we found reduced microphytobenthic biomass in summer, which were explained by increased evaporation/desiccation rates as a consequence of increased radiation, despite frequent tidal inundation. In conclusion, the observed density shifts in the benthic microbial communities are attributable to physical forcings dependent upon seasonal variations in interplaying factors such as sediment temperature, solar radiation and tidal inundation.